A Subfamily of Univalent Functions Associated with q-Analogue of Noor Integral Operator - Muhammad Arif; Miraj Ul Haq; Jin-Lin Liu (Journal of Function Spaces)
The main objective of the present paper is to define a new subfamily of analytic functions using subordinations along with the newly defined q-Noor integral operator. We investigate a number of useful properties such as coefficient estimates, integral representation, linear combination, weighted and arithmetic means, and radius of starlikeness for this class.